2008
DOI: 10.1177/1090198108315366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Implementation and Fidelity of Evidence-Based Behavioral Interventions for HIV Prevention: Lessons Learned From the Focus on Kids Diffusion Case Study

Abstract: Evidence-based interventions (EBIs) are used in public health to prevent HIV infection among youth and other groups. EBIs include core elements, features that are thought to be responsible for the efficacy of interventions. The authors evaluate experiences of organizations that adopted an HIV-prevention EBI, Focus on Kids (FOK), and their fidelity to the intervention's eight core elements. A cross-sectional telephone survey was administered to 34 staff members from organizations that had previously implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 16 publications
4
61
0
Order By: Relevance
“…Prior work examining HIV program fidelity has identified a number of fidelity challenges at the program level (e.g., training, client fit, procedural fit) [13,14,17,[24][25][26][27][28][29]. However, past studies have not examined how agencies adapt to economic strains and the influence of those adaptations on program fidelity.…”
Section: Program Fidelitymentioning
confidence: 99%
“…Prior work examining HIV program fidelity has identified a number of fidelity challenges at the program level (e.g., training, client fit, procedural fit) [13,14,17,[24][25][26][27][28][29]. However, past studies have not examined how agencies adapt to economic strains and the influence of those adaptations on program fidelity.…”
Section: Program Fidelitymentioning
confidence: 99%
“…9,10 and when it addresses the core characteristics of effective evidence-based programs for all adolescents, 11 as well as those at risk for 12 or living with HIV. [13][14][15][16] Evidence indicates that effective programs promote moral values, foster the development of relationships, and focus on the future by applying learning in real-life settings within the context of developing a social identity, and offer a sense of empowerment and self-care.…”
Section: Introductionmentioning
confidence: 99%
“…It focused on specific essential elements of effective programs, which were theoretically grounded, structured, accurate, and targeted several systems simultaneously. [9][10][11][12][13][14][15][16] This paper describes the community-based participatory research that informed the adaptation of the FACE intervention and presents the feasibility and acceptability outcomes as measured by enrollment, attendance, retention, satisfaction, tolerability, and positive and negative emotions…”
Section: Introductionmentioning
confidence: 99%
“…Adapted interventions that complement the intrinsic values and norms of the community have an increased chance of being institutionalized (Arthur & Blitz, 2000;Glaser & Backer, 1977;Rogers, 1995). Thus, it has been suggested that the major goal when adapting interventions should be to maintain the core elements that are thought to account for the positive outcomes, while adapting the EBI to the unique circumstances and preferences of the relevant audience and setting (Center for Substance Abuse Prevention, 2002;Galbraith et al, 2009;McKleroy et al, 2006). The need to balance fidelity of implementation with adaptation necessitated guidance for agencies on adaptation of EBIs.…”
mentioning
confidence: 99%
“…However, the empirical literature has underscored the importance of maintaining a high degree of fidelity of the original intervention components during program implementation. Nonetheless, EBIs are frequently altered during implementation (Botvin, 2004;Galbraith et al, 2009;Tappe, Galer-Unti, & Bailey, 1995) to target different risk behaviors, meet the needs of different sub-populations, due to agency capacity, or to increase community ownership of the program (Center for Substance Abuse Prevention, 2002;Berman & McLaughlin, 1976;Rogers, 1995). Adapted interventions that complement the intrinsic values and norms of the community have an increased chance of being institutionalized (Arthur & Blitz, 2000;Glaser & Backer, 1977;Rogers, 1995).…”
mentioning
confidence: 99%